Technology entrepreneurship : taking innovation to the marketplace - Thomas N. Duening (2024)
Technology Entrepreneurship' provides a practical toolkit for potential entrepreneurs with technology backgrounds that will help them navigate complex issues such as raising capital, IP protection, product development, and more. The book's structure follows the entrepreneurial process in a step-by-step way, defining key terms and helping readers without business qualifications engage with the activities addressed. In addition, it covers a discussion of current trends and developments relevant for tomorrow's entrepreneurs. In-depth information on the practicalities of technology entrepreneurship are combined with experience from academics to provide a unique resource on how to approach this crucial subject